Development and validation of a prognosis prediction model based on 18 endoplasmic reticulum stress-related genes for patients with lung adenocarcinoma - Shu, Long; Liu, Shuang; Tao, Yongguang (Frontiers in Oncology, 2022)
Background: Endoplasmic reticulum (ER) stress had a crucial impact on cell survival, proliferation, and metastasis in various cancer. However, the role of ER stress in lung adenocarcinoma remains unclear. Method: Gene expression and clinical data of lung adenocarcinoma (LUAD) samples were extracted from the Cancer Genome Atlas (TCGA) and three Gene Expression Omnibus (GEO) datasets. ER stress score (ERSS) was constructed based on hub genes selected from 799 ER stress-related genes by LASSO regression. A Cox regression model, integrating ERSS and the TNM stage, was developed to predict overall survival (OS) in the TCGA cohort and was validated in GEO cohorts. GSEA, ssGSEA, and gene mutation analyses were performed to further understand the molecular features of ERSS. The tumor immune infiltration was evaluated by ESTIMATE, CIBERSORT and xCell algorithms. The ROC curves were used to evaluate the predictive value of the risk model. P<0.05 was considered statistically significant. Results: One hundred fifty-seven differentially expressed genes (DEGs) were identified between tumor and para-carcinoma tissues and forty-five of them significantly correlated with OS. Next, we identified 18 hub genes and constructed ERSS by LASSO regression. Multivariate analysis demonstrated higher ERSS (P<0.0001, HR=3.8, 95%CI: 2.8-5.2) and TNM stage (P<0.0001, HR=1.55, 95%CI: 1.34-1.8) were independent predictors for worse OS. The prediction model integrating ERSS and TNM stage performed well in TCGA cohort (AUC at five year=0.748) and three GEO cohorts (AUC at 5 years=0.658, 0.717, and 0.739, respectively). Pathway enrichment analysis showed that ERSS significantly correlated with unfolded protein response. Meanwhile, pathways associated with cell cycle, growth, and metabolism were significantly enriched in the high ERSS group. Patients with SMARCA4, TP53, and EGFR mutation showed significantly higher ERSS (P=4e-04, 0.0027, and 0.035, respectively). Tissues with high ERSS exhibited significantly higher infiltration of M1 macrophages, activated dendritic cells and lower infiltration of CD8+T cells and B cells, which indicates an activated tumor antigen-presenting but suppressive immune response status. Conclusion: We developed and validated an ER stress-related risk model that exhibited great predictive value for OS in patients with LUAD. Our work also expanded the understanding of the role of ER stress in LUAD.